CLINICO-IMMUNOLOGIC AND CYTOGENETIC ASPECTS OF PATHOGENESIS IN SPASTIC INFANTILE CEREBRAL PARALYSIS - D. D. Gaynetdinova; L. Z. Gaysina; R. F. Khakimova (Медицинская иммунология, 2014)
Abstract. Over recent years of studies in infantile cerebral paralysis (ICP), the changes in periventricular area are given great importance, especially, periventricular leukomalacia. An immunopathological process may define the prenatal brain damage. We performed a clinicalytogenetic and immunological evaluation, including subpopulation analysis of lymphocytes, functional activity of phagocytes, quantitative content of TNFα in blood serum and saliva in thirty-five ICP patients (1 to 4 years old). This study has shown suppression of cellular immunity, increase in oxidation/reduction activity of neutrophils, and increased TNFα levels in peripheral blood serum and salivary fluid in cases of periventricular leukomalacia that resulted into ICP. An interrelation was revealed between the levels of genome instability and TNFα content, thus suggesting involvement of active immunopathological processes in those patients with ICP who develops periventricular leukomalacia.